Vascular-metabolic and GABAergic Inhibitory Correlates of Neural Variability Modulation. A Combined fMRI and PET Study. (21st May 2018) - Qin, Pengmin; Duncan, Niall W.; Chen, David Yen-Ting; Chen, Chi-Jen; Huang, Li-Kai; Huang, Zirui; Lin, Chien-Yuan E.; Wiebking, Christine; Yang, Che-Ming; Northoff, Georg; Lane, Timothy J.
Highlights: Occipital cortex temporal variability reduces from eyes open to closed. This is correlated with an increase in energy consumption in the region. Variability reduction is correlated with regional GABAA receptors. Show in humans that BOLD temporal variability changes involve GABAA-mediated inhibition. Abstract: Neural activity varies continually from moment to moment. Such temporal variability (TV) has been highlighted as a functionally specific brain property playing a fundamental role in cognition. We sought to investigate the mechanisms involved in TV changes between two basic behavioral states, namely having the eyes open (EO) or eyes closed (EC) in vivo in humans. To these ends we acquired BOLD fMRI, ASL, and [ 18 F]-fluoro-deoxyglucose PET in a group of healthy participants ( n  = 15), along with BOLD fMRI and [ 18 F]-flumazenil PET in a separate group ( n  = 19). Focusing on an EO- vs EC-sensitive region in the occipital cortex (identified in an independent sample), we show that TV is constrained in the EO condition compared to EC. This reduction is correlated with an increase in energy consumption and with regional GABAA receptor density. This suggests that the modulation of TV by behavioral state involves an increase in overall neural activity that is related to an increased effect from GABAergic inhibition in addition to any excitatory changes. These findings contribute to our understanding of the mechanisms underlying activity variability in the human brain and its control.